Do couples pool their income? Evidence from demand system estimation for Germany - Martin Beznoska (Freie Universität Berlin, School of Business & Economics, 2019)
Whether couples pool their resources and behave like a unit or spend their income individually is crucial for social and tax policy. In this paper, I provide a test of the income pooling hypothesis using administrative cross-sectional survey data on expenditures and individual incomes of couple households in Germany. The test is performed within the Quadratic Almost Ideal Demand System (QUAIDS) framework, which allows for an endogenous expenditure budget and endogenous individual income contribution shares in an instrumental variables approach. Although the hypothesis is broadly rejected, there are significant differences regarding the marital status, the presence of at least one child in the household and whether the household is located in a former West or East German federal state. Married couples and couples with children are closer to the acceptance of the hypothesis than unmarried couples without children.
urn:nbn:de:kobv:188-refubium-23920-6
Keywords: D12; D13; H24; J12; 330; Income Pooling; Intra-Household Allocation; Consumer Demand; QUAIDS